Contracts for Cooperation between Web Service Programmers and HTML Designers - Böttger, Henning; Møller, Anders; Schwartzbach, Michael I. (BRICS Report Series, 2003)
Interactive Web services consist of a mixture of HTML fragments and program code. The fragments, which are maintained by designers, are combined to form HTML pages that are shown to the clients. The code, which is maintained by programmers, is executed on the server to handle the business logic. Current Web service frameworks provide little help in separating these constituents, which complicates cooperation between programmers and HTML designers. We propose a system based on XML templates and formalized contracts allowing a flexible separation of concerns. The contracts act as interfaces between the programmers and the HTML designers and permit tool support for statically checking that both parties fulfill their obligations. This ensures that (1) programmers and HTML designers work more independently focusing on their own expertises, (2) the Web service implementation is better structured and thus easier to develop and maintain, (3) it is guaranteed that only valid HTML is sent to the clients even though it is constructed dynamically, (4) the programmer uses the XML templates consistently, and (5) the form input fields being sent to the client always match the code receiving those values. Additionally, we describe tools that aid in the construction and management of contracts and XML templates.